Rivers - Burnham, Laurie; Nash, Geoffrey H. (New York : Chelsea House, 2007)
Presents an introduction to rivers, describing how they were formed and how they have changed over time, and provides the history and description of ten of the world's most famous rivers.
Origin of the landform: Rivers -- Nile, Africa -- Amazon, South America -- Yangtze, Asia -- Mississippi, North America -- Huang Ho, Asia -- Yenisey, Asia -- Ob', Asia -- Congo River, Africa -- Amur River, Asia -- Mackenzie River, North America -- Glossary -- Books -- Magazines -- Web sites -- Index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Rivers; Electronic books; Electronic books